2020
DOI: 10.1002/ps.5723
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory selection, resistance risk assessment, multi‐resistance, and management of Tetranychus urticae Koch to bifenthrin, bifenazate and cyflumetofen on cowpea

Abstract: BACKGROUND Tetranychus urticae (T. urticae) Koch is an important pest of vegetable crops worldwide. In this study, bioassays were carried out to analyze the resistance risk, multi‐resistance and management of T. urticae Koch to bifenthrin, bifenazate and cyflumetofen on cowpea. RESULTS The resistance ratios of the adult T. urticae population to bifenthrin (G16), bifenazate (G12) and cyflumetofen (G12) were 31.29, 9.38 and 5.81, respectively. Realized heritability (h 2) analysis showed that, under a selection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…In the current study, the HD-BJ population had the lowest resistance to cyflumetofen and cyenopyrafen among the tested field populations; the HD-BJ population also had the lowest levels of activity of P450 and CarEs. This is consistent with previous reports that P450 and CarEs are jointly involved in resistance to cyflumetofen (Riga et al, 2015;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the current study, the HD-BJ population had the lowest resistance to cyflumetofen and cyenopyrafen among the tested field populations; the HD-BJ population also had the lowest levels of activity of P450 and CarEs. This is consistent with previous reports that P450 and CarEs are jointly involved in resistance to cyflumetofen (Riga et al, 2015;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that the LC 50 values of cyflumetofen, cyenopyrafen and B‐azolemiteacrylic, which function as respiratory chain complex inhibitors, ranged 1–52 mg/L among the seven field populations. Cyflumetofen is a semi‐esterase‐dependent precursor acaricide, which acts as a complex II inhibitor in the mitochondrial electron transport chain; previous research revealed that when esterase activity is inhibited, the toxicity of cyflumetofen is greatly reduced (Liu et al ., 2020). In the current study, the HD‐BJ population had the lowest resistance to cyflumetofen and cyenopyrafen among the tested field populations; the HD‐BJ population also had the lowest levels of activity of P450 and CarEs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we suspect that other resistance mechanisms are involved in the resistance of the tested T. urticae populations to bifenthrin. In support of that possibility, mixed-function oxidase (MFO) was reported to be important for the bifenthrin resistance of T. urticae on cowpea in China [28]. The five T. urticae populations in the current study were moderately resistant to the organophosphate profenofos, even though the frequencies of G119S and A201S mutations, which are important for organophosphate resistance [29], ranged from 20% to 92% and from 2% to 80%, respectively.…”
Section: Prudent Application Of Traditional Pesticides Due To Medium ...supporting
confidence: 61%